Resolution of the large middle fossa arachnoid cyst without any identifiable cause: Case report. (June 2021) - Kikuchi, Asami; Chernov, Mikhail; Hagiwara, Shinji; Ohbuchi, Hidenori; Kubota, Yuichi; Kasuya, Hidetoshi
Highlights: Few reports document spontaneous regression of intracranial arachnoid cysts. Intracranial arachnoid cysts may regress spontaneously without any clear cause. Observation of intracranial arachnoid cysts without mass effect is reasonable. Abstract: Although the possibility of spontaneous regression of intracranial arachnoid cysts (AC) during observational follow-up is widely recognized, the number of reports documenting such clinical course, often associated with the mild head trauma, is rather limited. We present a case of nearly complete resolution of the large middle fossa AC in a 5-year-old boy without any identifiable cause in 2.3 years after the initial diagnosis. It once again justifies observational strategy for AC not accompanying by mass effect and manifesting with minimal symptoms or diagnosed incidentally.